Novel RNA viruses from the native range of Hymenoscyphus fraxineus, the causal fungal agent of ash dieback - Shamsi, Wajeeha; Kondo, Hideki; Ulrich, Sven; Rigling, Daniel; Prospero, Simone (Virus research, 2022)
•Five mycoviruses were detected in two native populations of Hymenoscyphus fraxineus.•The overall virus prevalence in the Japanese populations was 11.2%.•All the reported viruses belong to new species in their respective genera.•A mitovirus with two genomic forms (linear and circular) was characterized. The native Japanese population of the fungus Hymenoscyphus fraxineus, the causal agent of ash dieback in Europe, was screened for viruses using a high-throughput sequencing method. Five RNA viruses were detected in 116 fungal isolates sequenced via Illumina RNA-seq platform, with an overall virus prevalence of 11.2%. The viruses were completely sequenced by RNA ligase mediated rapid amplification of cDNA ends (RLM-RACE) followed by Sanger sequencing. The sequences appear to represent new species from three established families (Mito-, Endorna- and Partitiviridae), one recognized genus (Botybirnavirus) and a negative-sense single-stranded RNA virus in the order Bunyavirales from the proposed family “Mybuviridae”. The highest prevalence was found for the mitovirus (7.8%), that had two genomic forms (linear and circular), while the other viruses were detected each in one isolate. Co-infection of a mitovirus and an endornavirus was also observed in one of the infected isolates. Here we describe the molecular characterization of the identified viruses. This study expands the diversity of viruses in H. fraxineus and provides the basis for investigating the virus-mediated control of ash dieback in Europe.